(untitled) (St. Louis, Mo., 2004)
Mosby’s dental dictionary contains approximately 2100 definitions that have become relevant to these fields. Definitions for words commonly used in immunology, microbiology, radiography, special needs dentistry, pediatric dentistry, anesthesiology, and common medicine, as well as terminology from the legal and insurance fields with which a hygienist or assistant should be speech. Synonyms are included where applicables to help users understand terms,...
Keywords: Dentistry,Dentistry; English